Hubungan Pengetahuan Ibu dengan Kepatuhan Pemeriksaan Perkembangan Kehamilan di Puskesmas Dusun Baru - Zuhairoh Zuhairoh; Yatri Hilinti; Liya Lugita Sari (Jurnal Pakar Kesehatan, 2026)
Pregnant women’s knowledge of pregnancy plays a crucial role in the early detection of pregnancy warning signs; thus, if a woman is aware of these warning signs and is experiencing them, she can promptly decide on the necessary actions to minimize the risk of complications and the worsening of her condition. The objective of this study is to determine the relationship between a mother’s knowledge and her adherence to prenatal checkups at the Dusun Baru Community Health Center. This study employed an analytical research design using a cross-sectional study. The study was conducted at the Dusun Baru Community Health Center from June 15 to December 30, 2025. The sample for this study consisted of the entire population (total sampling), specifically pregnant women in the late third trimester (36 weeks’ gestation) who underwent prenatal checkups at the Dusun Baru Community Health Center, totaling 30 individuals. The analyses employed were univariate and bivariate using the chi-square test. The results of the study showed a significance level of α = 0.05, with a p-value of 0.012 < 0.05; therefore, it can be concluded that there is a relationship between maternal knowledge and adherence to prenatal check-ups. The researcher recommends that the Dusun Baru Community Health Center enhance its health promotion and education efforts for pregnant women regarding the importance of regular prenatal check-ups in accordance with antenatal care (ANC) service standards.